2015
DOI: 10.1007/s00710-015-0388-0
|View full text |Cite
|
Sign up to set email alerts
|

Petrogenesis of Mesoproterozoic lamproite dykes from the Garledinne (Banganapalle) cluster, south-western Cuddapah Basin, southern India

Abstract: We report mineral chemistry and whole-rock major and trace-element geochemistry for a recent find of Mesoproterozoic (~1.4 Ga) lamproites from the Garledinne (Banganapalle) cluster, south-western part of the PaleoMesoproterozoic Cuddapah Basin, southern India. The Garledinne lamproites occur as WNW-ESE-trending dykes that have undergone varying degree of pervasive silicification and carbonate alteration. Nevertheless, their overall texture and relict mineralogy remain intact and provide important insights into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…(A) Generalised geological map of India showing the location of the Thanewasna lamprophyre (study area (box)) in the western margin of the Bastar Craton, central India. The occurrence of other lamproites and kimberlites in various cratons is also shown after Chalapathi Rao et al (2016) and (B) geological map of the Thanewasna lamprophyre in the WBC (Dora et al 2017).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…(A) Generalised geological map of India showing the location of the Thanewasna lamprophyre (study area (box)) in the western margin of the Bastar Craton, central India. The occurrence of other lamproites and kimberlites in various cratons is also shown after Chalapathi Rao et al (2016) and (B) geological map of the Thanewasna lamprophyre in the WBC (Dora et al 2017).…”
mentioning
confidence: 90%
“…In India, lamprophyres occur in the rocks of various ages, tectonic settings and cratonic areas (Fareeduddin and Mitchell 2012). In the Bastar Craton lamprophyres, lamproite and kimberlite are known to occur in the eastern parts (Mainkar et al 2004;Lehmann et al 2010;Chalapathi Rao et al 2016); however, lamprophyres have not been so far reported from the Western Bastar Craton (WBC). In this communication, a new occurrence Figure 1.…”
mentioning
confidence: 99%
“…The Palaeoproterozoic Indian shield subsequently broke up and reassembled in the subsequent supercontinent cycles (Rodinia and Gondwana; reviewed in Meert & Torsvik, 2003;Brown, 2007;Li et al 2008;Bhowmik et al 2012;Sengupta et al 2015;Dasgupta et al 2013a;Chattopadhyay et al 2015;Olierook et al 2019). The Indian shield including the CGGC has been punctured by multiple phases of alkaline magmatism with or without carbonatite (reviewed in Paul et al 2020) and kimberlite/lamproite/lamprophyre (reviewed in Chalapathi Rao et al 2004Rao et al , 2012Rao et al , 2020Rao et al 2016;Sharma et al 2019) that spread over a long stretch of time after the formation of the Indian shield as a part of the Columbia supercontinent. Geochemical and radiogenic isotope data from >1000 Ma kimberlite/lamproite/lamprophyre and the entrained perovskite support the existence of a metasomatized SCLM where DM was the chief component with variable contributions from the asthenospheric mantle (Rao et al 2016;Sharma et al 2019).…”
Section: A1 Geochemical Proxy Of the Studied Rock: Source Characteris...mentioning
confidence: 99%
“…Zachariah et al (1999) proposed 1756±29 Ma, Pb-Pb date of the dolomite hosted Ur mineralized horizons of Vempalle and Tadpatri Formation. An upper age constraint of 1400 Ma for the Cuddapah deposition is provided by the ages for lamproite dykes intrusive to Cumbum shale, between 1354 and 1418 Ma (Chalapathi Rao et al, 2016Rao et al, , 1996Kumar et al, 2001). The uppermost limit of the sedimentation in the Kurnool Group is assumed to be >1.1Ga, based on the carbonate and limestone xenoliths that were presumably derived from these horizons and hosted the 1.1 Ga Siddanpalle kimberlites of the Raichur kimberlite Field (Chalapathi Rao et al, 2010).…”
Section: Cuddapah Basinmentioning
confidence: 99%